2001
DOI: 10.1038/sj.ijo.0801667
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipids, serum insulin, plasma fibrinogen and aerobic capacity in obese and non-obese Singaporean boys

Abstract: OBJECTIVES:To compare blood lipids, lipoproteins, apoproteins, ®brinogen, insulin and aerobic capacity in obese and nonobese Chinese Singaporean boys. To examine relationships between blood metabolites, body composition and aerobic capacity in these groups. DESIGN: Cross-sectional SUBJECTS: Forty Chinese Singaporean boys aged 13 ± 15 y. Classi®ed as obese (n 20) or non-obese (n 20) based on adiposity (fat massafat free mass): b 0.60 obese,`0.40 non-obese. MEASUREMENTS: Body composition (dual energy X-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
13
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
5
13
1
4
Order By: Relevance
“…These Bengali obese children hence have every possibility of developing type 2 diabetes in near future. It is supported firmly by similar results from a number of previous studies abroad by Garcés et al [13], Stencel et al [14], Shea et al [16] and in north India by Misra et al [17]. The prevalence of hyperinsulinemia is higher in the present study compared to the study in UK children [12] (61% vs. 40%, p<0.05).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These Bengali obese children hence have every possibility of developing type 2 diabetes in near future. It is supported firmly by similar results from a number of previous studies abroad by Garcés et al [13], Stencel et al [14], Shea et al [16] and in north India by Misra et al [17]. The prevalence of hyperinsulinemia is higher in the present study compared to the study in UK children [12] (61% vs. 40%, p<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The previous studies have shown correlation of high BMI with high TG and low HDL only [13,14]. But in the present study a high significant correlation has been found between BMI and each of CH, LDL, TG and HDL, as well as between each of the lipid fractions indicating the risk of obesity induced dyslipidemia.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…When adjusting for physical activity the significant difference in fibrinogen between the sexes remained, but adjustment for body fat percentage resulted in an insignificant difference in fibrinogen, indicating that the sex difference observed may be attributed to the girls having a significantly higher body fat percentage than the boys. Literature shows that plasma fibrinogen concentration is positively associated with anthropometric markers for body fat in boys and girls [19,49]. Halle et al [50] found significantly higher concentrations of the inflammatory parameters such as fibrinogen, interleukin-6 and tumour necrosis factoralpha in obese children when compared with nonobese children.…”
Section: Discussionmentioning
confidence: 99%
“…26 A research in Singaporean adults has revealed a relationship between BMI, abdominal diameter and insulin resistance. 26,27 It has been reported that in children and adolescents the measurement of fasting insulin levels in the presence of normoglycaemia may be an indicator of IR, which is as good as HOMA-IR, FGIR and QUICKI. 22 However the variability of insulin measurements between laboratories makes it difficult in comparing the insulin levels obtained from different studies.…”
Section: Discussionmentioning
confidence: 99%